2020
DOI: 10.1542/peds.2019-3901
|View full text |Cite
|
Sign up to set email alerts
|

Parent Preferences for Pediatric Clinician Messaging to Promote Smoking Cessation Treatment

Abstract: BACKGROUND AND OBJECTIVES: Insights from behavioral economics suggests that the effectiveness of health messages depends on how a message is framed. Parent preferences for smoking cessation messaging has not been studied in pediatrics, warranting further exploration to maximize benefit. We sought to assess parents' perceptions regarding the relative importance of distinct message framings to promote their smoking cessation.METHODS: We conducted a cross-sectional discrete choice experiment in which parent smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Participant interactions with iterative system prototypes helped identify how to make these key functions acceptable and usable. Parents valued motivational messages, informed by behavioral science, that focused on the benefits of smoking cessation to their child's health 11,12 and simple, easy-to-understand explanations of treatment options. Pediatric clinicians valued automation of parent screening, treatment, and documentation with simple guidance on key conversation prompts that support treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participant interactions with iterative system prototypes helped identify how to make these key functions acceptable and usable. Parents valued motivational messages, informed by behavioral science, that focused on the benefits of smoking cessation to their child's health 11,12 and simple, easy-to-understand explanations of treatment options. Pediatric clinicians valued automation of parent screening, treatment, and documentation with simple guidance on key conversation prompts that support treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric settings, tobacco use treatment messages that emphasize the impact of smoking to parents on their child may increase acceptance of cessation treatment. 11 12 Effective messages and interventions for parental tobacco use treatment can be systematized through electronic health records' (EHRs') clinical decision support (CDS) systems. These systems are effective in improving health care process measures across a wide variety of care settings.…”
Section: Background and Significancementioning
confidence: 99%
“…Jenssen et al 11 showed that parent smokers identified the most important smoking cessation message for motivating a smoking cessation attempt to be those that emphasized the impact on their child's health. The fact that parents of children suffering from respiratory disease were more likely to quit smoking may, therefore, be a consequence of their concern for their child's respiratory health.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatricians can be particularly influential since they intervene at the time when parents are seeking to improve their child's state of health. As recently established by Jenssen et al, 11 the benefit on their child's health is the main motivation for parents to quit smoking.…”
Section: Introductionmentioning
confidence: 93%
“…In pediatric settings, tobacco use treatment messages to parents that emphasize the impact of smoking on their child may increase acceptance of cessation treatment. 11,12 Prior research suggests that messages to parents about their smoking should focus on child health rather than, for example, the financial impact of smoking. 11 Incorporating foundational elements of motivational interviewing, framing conversations to address concerns unique to parents, can increase engagement and intrinsic motivation as well as perceived clinician empathy.…”
Section: Background and Significancementioning
confidence: 99%